2019
DOI: 10.1002/ejlt.201800457
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Sunflower Oil with γ‐Tocopherol. Study by 1H NMR of Its Effect Under Accelerated Storage Conditions

Abstract: The effect of the enrichment of sunflower oil with γ‐tocopherol on the evolution of its oxidation is the subject of this study. Sunflower oil and samples of this oil enriched with different γ‐tocopherol concentrations are submitted to accelerated storage conditions and their evolution, until total polymerization is monitored by 1H NMR spectroscopy. The concentrations of linoleic acyl groups, of primary and of a great number of secondary oxidation compounds are determined throughout the process. These concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…Such protection can be understood and explained by the capacity of the antioxidants to scavenge free radicals (via electro paramagnetic resonance spectroscopy) that are responsible for the oxidative destruction of lipids, nucleic acids, and proteins ( Chemat et al, 2000 , Espín et al, 2000 ). Electro paramagnetic resonance spectroscopy has found a wide variety of applications in detecting free radicals owing to its high sensitivity to unpaired electrons Martínez-Yusta and Guillén (2019) . The close interaction of DPPH with the free radical scavengers present in the enriched flaxseed oil presented a reduced signal intensity relative to pure flaxseed oil and DPPH stock solution EPR spectra ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such protection can be understood and explained by the capacity of the antioxidants to scavenge free radicals (via electro paramagnetic resonance spectroscopy) that are responsible for the oxidative destruction of lipids, nucleic acids, and proteins ( Chemat et al, 2000 , Espín et al, 2000 ). Electro paramagnetic resonance spectroscopy has found a wide variety of applications in detecting free radicals owing to its high sensitivity to unpaired electrons Martínez-Yusta and Guillén (2019) . The close interaction of DPPH with the free radical scavengers present in the enriched flaxseed oil presented a reduced signal intensity relative to pure flaxseed oil and DPPH stock solution EPR spectra ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, alpha tocopherol exhibits a prooxidant effect, which increases in line with its concentration, whereas gamma-tocopherol only accelerates oxidation at very early oxidation stages. However, the global effect in the total oxidation process could be considered antioxidant [7][8][9].…”
Section: Study Of the Formation Of Oxidation Compounds During In Vitrmentioning
confidence: 99%
“…In spite of this, the knowledge of the effect that this enrichment provokes in foods when they are submitted to different processes is scarce. Recently, it has been shown that some compounds, attributed to antioxidant ability, act as prooxidants in some foods, when submitted to certain oxidative conditions [7][8][9]. Taking into account all of the above mentioned, the study of the effect of the enrichment of lipid foods with compounds, with potential antioxidant ability on their behavior during digestion, is important for both industry and consumers.…”
Section: Introductionmentioning
confidence: 99%
“…1 H NMR (proton nuclear magnetic resonance) spectroscopy has been used along with standard analysis to analyze oils and its compositions regarded to acylglycerols, fatty acid alkyl esters (FAAEs), its byproducts. 29 Martínez-Yusta et al 3 studied the sunflower oil degradation process with accelerated storage. Howell et al 30 investigated the steps of the castor oil degradation.…”
Section: Ana Carolina G Mantovani a Letícia Thaís Chendynski B Diego Galvan Cmentioning
confidence: 99%
“…There is also the possibility of the formation of decomposition products as: acids, aldehydes, esters, ketones, peroxides and alcohols. 3 In the degradation can occur the formation of gums that can clog the injection systems. Also, the hydroperoxides presence with high levels of acids from the oxidation can generate corrosion in the fuel system.…”
Section: Introductionmentioning
confidence: 99%